(3hUa eUQ HGdYHQj (B:s (3JaGUjd GdENJQGb GdESQGFjdj ddYbd GdeUQj (B/s - (3QaYJ, SjO CMeOs; (3YeGO Mdje(B;(3GdSjO YHO GdeYWjs ((3eUQ (B:s (3SjfG ddfTQ ,s, 1989)
(3hUa GdcGJH eUQ HGdYHQj (B"(3eSdSd GdENJQGb GdKbGaj h GdSjGSj GdESQGFjdj h YGTJg eUQ efP eHGOQI GdbOS (B1977 (3h MJi Gdjhe (B1988 (3adbO JZdZdhG aj cd TjA eMGhdjf JUOjQ GdhWf Gdi NGQLg h JMOjOG Gdi (B"(3hGTfWf(B" (3h Gdi Jd GHjH YHQ THcI ef GdeDSSGJ h GdgjFGJ GdZQHjI GdJj JfTL HQOG GdYde h GdKbGaI h dcfge aj hGbY GdCeQ LhGSjS aj KjGH GdYdeGA (B. (3JQi eG PG MOK Ydi hLg GdJMOjO? h eGgj JaGUjd h GSQGQ GdZMJQGb GdUgjhfj GdGeQjcj deUQ aj GdfhGJ GdYTQ GdeGVjI ? h cja GdSHjd Edi ehGLgJg ? Pdc gh (B"(3ehVhY gPG GdcJGH (B. s
Keywords: (3GdESQGFjd s; (3GdbGgQIs; (3eUQ s